Serbian adaptation of the Perceived Vulnerability to Disease (PVD) scale - Rokvic, Nikola; Karan, Vedrana (Engrami, 2022)
The year 2020 has shown the renewed importance of combating infectious diseases. Apart from the psychological immune system an individual possesses a behavioral immune system. Key components of this system are digest proneness, perceived vulnerability to disease, health anxiety, and others. There is no instrument to measure perceived vulnerability to disease in the Serbian language so we undertook this research to provide the scientific community with a viable tool for researching this relevant topic, the Perceived Vulnerability from Disease scale (PVD). On a sample of 500 participants, out of the 82.6% identified as female, and the average age of 20.53 (SD=1.27; min=19; max=26), we performed confirmatory factor analysis. Two existing models for the scales structure have not shown adequate model fit. Therefore, we have created a model that preserves the two-factor structure, the Perceived Infectability (PI) and the Germ Aversion (GA) subscales, but we had to lose two items to do so.  We have tested the scale alongside other relevant constructs to determine its divergent validity and have found satisfactory results. In conclusion, the Serbian translation of the PVD is a valid instrument and can be used for further research.
Keywords: PVD; disgust; validation